PENERAPAN MEDIA PEMBELAJARAN BIOLOGI DENGAN MENGGUNAKAN MACROMEDIA FLASH PROFESIONAL 8 - Karno, Ria (Universitas Pasir Pengaraian, 2015)
This study was aimed to of determine there isor not effect of Macromedia Flash Profesional 8 learning method toward student achievement of class X SMA Negeri 2 Tambusai learning year 2015 This was a quasi- experiment study with Non Randomized Control Group Pretest Posttest Design. Samples were collected with non random sampling method. The samples are the student at grade XA grade XB as experiment and as control. Data collecting technique in this study was a test instrument with multiple choice questions form. Hypothesis of results showed that the t (4,02>2,01). Inconclution that Macromedia Flash Profesional 8 learning method toward student achievement give effect toward student achievement of class X SMA Negeri 2 Tambusai learning year 2015.